Gateway of the Gypsies - Ozan, Pepe; Tchaicovsky, Melitta (ArtNetwork Productions, 2004)
Verzio FF Two American filmmakers follow the wanderings of a nomadic ethnic group in Northern India, in Rajasthan, in the Thar Desert. A series of short interviews, with minimal narration, carries the viewer through the life of communities which travel from village to village as their living space is narrowed down as a consequence of advancing modernity. The film presents the traditional activities of different tribes: the snakecharmers, storytellers, musicians, metalworkers, salt traders and dancers.